Risk factors to cause tooth formation anomalies in chemotherapy of paediatric cancers. (21st January 2013) - Nishimura, S.; Inada, H.; Sawa, Y.; Ishikawa, H.
Risk factors to cause tooth formation anomalies in chemotherapy of paediatric cancers This study aimed to investigate the risk factors of tooth formation anomalies in anti‐cancer chemotherapies. Long‐term survivors treated by conventional chemotherapy (n = 26), conventional chemotherapy with high‐dose chemotherapy (HDC) (n = 14), and HDC with total body irradiation (TBI) (n = 6) were analysed for the incidence of tooth agenesis, microdonts, and short‐rooted teeth. The tooth agenesis and/or microdonts were found in second premolars and second molars, but not in first molars or central incisors. The ratio of subjects with tooth agenesis and/or microdonts was 66.7% and 18.2% in subjects administered conventional chemotherapy at <4 years and ≥4 years of age, respectively, while it was 100% and 25% in subjects administered HDC at <4 years and ≥4 years of age. The incidence of tooth formation anomalies did not related with the duration of conventional chemotherapy but increased by HDC. The incidence of tooth formation anomalies did not show significantly differences between the HDC with and without TBI groups, and was higher in busulfan‐administered subjects than in subjects given cyclophosphamide. It may be concluded that the high‐risk group of tooth agenesis is the subjects with HDC under 4 years of age. However, protocols of conventional chemotherapy are not an important risk factor to cause the tooth formation anomalies.